Decolourization of Azo Dyes and Dye Industry Effluents by Lignin Degrading Fungus Trametes versicolor - Selvam, Dr K (International Journal of Pharmaceutical & Biological Archive, 2012)
Decolourization of Azo Dyes and Dye Industry Effluents by Lignin Degrading Fungus Trametes versicolor